Kadar Aspal Optimum Laston Lapis Aus Menggunakan Abu Jerami Sebagai Pengganti Filler - Nikodemus Tandung; Rais Rachman; Alpius (Paulus Civil Engineering Journal, 2021)
Asphalt as a binder in the LASTON mixture in flexible pavement system has very important influence on design life of the pavement. Therefore, the use of asphalt content is very important as well as the use of straw waste as filler substitute.The method this study is in accordance with the specifications the Bina Marga 2018. The results showed that all the characteristics of the mixture, stability, flow, VIM, and VFB meet the Bina marga 2018 specifications and VMA at asphalt levels of 5.0% -5.5% don’t meet specifications and VMA at asphalt levels 6.0% -7.0% meets specifications. Where the asphalt content used is 5.0%, 5.5%, 6.0%, 6.5%, and 7.0%. The optimum asphalt content obtained is asphalt content 7.0%.